Academic attitudes toward new media: An exploratory multidisciplinary study. Issue 1 (1st January 2016) - Menzies, Kathleen; Johnson, Frances
ABSTRACT: This article looks at the attitudes of UK academics toward new media, utilizing organizational and sociocultural understandings of fields of scholarly enquiry. It focuses on four traditionally distinct disciplines—art and design, computer science, health science, and politics and international relations—representative of the range of approaches in higher education. Agreement was found among respondents across disciplinary communities about what new media represent and how they support their work. Analysis of semantic differential charts identified two dimensions underlying attitudes—"flexibility" and "fitness for scholarly purposes." Rather than being anchored by epistemological divisions, new media are assessed by practical viewpoints relating to the activity types they allow, and by traditional measures of reliability. In response to questions about other characteristics of their disciplines (such as reputation and audience diversity), distinctions are in evidence, although in some cases these are not traditional ones.